Optimizing Organization Design Using Three Level Analysis of Organization at Engineering Division PT Bina Reka Cipta Utama - Tawekal, Rio Lukman; Welly, John (Journal of Business and Management, 2016)
Abstract. PT. Bina Rekacipta Utama is an engineering consultant company at oil and gas industry. The owner of the company stated that the employee turnover rate was high and the owners wants fix the problem. The aim of this research was to analyzed motivation level of the employees because individual motivation has significance relation with turnover rate and employee performance. Since PT. Bina Rekacipta Utama is a service company, the engineers are the core of the company. If the employee performance of the engineers can be increase, the company performance also will increase. This research conducted using descriptive analysis and quantitative analysis for the correlation each variable to employee performance. To improve the management system, the researcher wants to analyze the engineering division because this division is the core of the company. The researcher tries to analyze 3 level of organization; Organization level, Team Level, Individual level. And create an organization model for PT. Bina Rekacipta Utama by using the data that have been gathered from the company as an evaluation material to fix its organization model. The researcher used 7S McKinsey organization model because it is the most simple and popular organization model to apply it at PT. Bina Rekacipta Utama Hopefully after the research is conducted the result can be used for PT. Bina Rekacipta Utama evaluation material.Ã‚Â Keyword Ã¢â‚¬â€œ Redesign Organization